Kilka uwag o rzymskich Itinerariach (VII wiek) - Pawłowska-Blachaczek, Beata (Vox Patrum, 2008)
Roman Itineraries were written to make visiting sacred places easier in the Eternal City. The oldest ones originated in the 7th century, when the Roman cata-combs were still visited, just before the times of mass relocation of martyrs’ relics to European churches. Therefore, they are a source of information about the condition of Roman sacred places at the close of Christian antiquity. AU of them are indexes and catalogues informing where loca sancta can be found, how to get to them and what is worth seeing. The marked routes for pilgrims seem to be standard ones, along which the arrivals were led. The description of topography of Rome based on Itineraries allows us to learn about the places where martyrs’ remains were buried; showing a specific place where they were worshipped by the arrivals to the Eternal City in the 7th century. It should be emphasized that in some cases they differ while describing the location of martyrs’ burial grounds.